PERAN PEPOHONAN DALAM PENINGKATAN PRODUKSI TERNAK RUMINANSIA: PENDEKATAN ILMIAH - Mastika, I.M; Puger, A.W.; Budiasa, I.K.M.; Nuriyasa, M. (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak; Vol 2 No 2, 2014)
Trees and shrubs plantation are very potential and important in producing sustainable green biomass, and have high protein content and high digestibility.  Some of them are legume which are important in catching nitrogen from the air to enriched the soil nitrogen. Trees are also catching more sun energy radiation which is latter converted into animal feeds. Other roles of this plant is part of them such as leaves, fruits, barks and roots containing saponin/sapogenin or tannin which are useful as defaunating agent. It was well documented that rumen protozoa reduced ruminant productivity. From the reports available either in vitro or in vivo it was proved that saponin could to some extent reduced or depressed protozoa rumen population. Indonesia needs some  experts effort to identify and recording those plants that could play roles as natural defaunating agent, as well as provide green biomass for ruminant. The overall conditions above will provide an ample opportunities for research for students or experties.
Keywords: tree plantations, defaunating agent, saponin/sapogenin, rumen protozoa